Assessing the Impact of COVID-19 on the Financial Health of Health Insurance Companies in India - Vasani Sureshbhai V (Educational Administration: Theory and Practice, 2024)
The COVID-19 pandemic has increased healthcare costs, making it crucial to purchase insurance to protect oneself and their families. To ensure fair treatment and protect policyholders, insurance companies must analyse their performance using the CARAMEL model. This study focuses on selected health insurance service providers in India, collecting data from annual reports, Particulars Company's website, and IRDA's website. The study evaluates the performance of Indian health insurance companies using various ratios and statistical methodologies. Star Health & Allied Insurance Company Ltd. received the highest gross direct premium, while Aditya Birla Health Insurance Co. Ltd. received a lower gross premium. Stand-alone and public health insurance companies performed better in terms of net premiums. The CARAMEL model showed notable significant differences between 2016 and 2022, with the only United India insurance company showing a partial positive correlation. The overall regression analysis resulted in three key ratios: capital adequacy, asset quality, and risk retention. Results show a notable significant difference in gross premiums before-after the pandemic, but also a decrease in various ratios, suggesting a need for financial stability and health improvement. Star health insurance companies ranked highest.